The Sparsholt affair - Hollinghurst, Alan (Alfred A. Knopf, 2018)
"From the internationally acclaimed winner of the Man Booker Prize, a masterly new novel that spans seven transformative decades in England--from the 1940s to the present--as it plumbs the richly complex relationships of a remarkable family. In 1940, David Sparsholt arrives at Oxford to study engineering, though his sights are set on joining the Royal Air Force. Handsome, athletic, charismatic, he is unaware of his effect on others--especially on Evert Dax, the lonely son of a celebrated novelist who is destined to become a writer himself. With the world at war, and the Blitz raging in London, Oxford nevertheless exists at a strange remove: a place of fleeting beauty--and secret liaisons. A friendship develops between these two young men that will have unexpected consequences as the novel unfolds. Alan Hollinghurst's new novel explores the legacy of David Sparsholt across three generations, on friends and family alike; we experience through its characters changes in taste, morality, and private life in a sequence of vividly rendered episodes: a Sparsholt holiday in Cornwall; eccentric social gatherings at the Dax family home; the adventures of David's son Johnny, a painter in 1970s London; the push and pull in a group of friends brought together by art, literature, and love. And evoking the increasing openness of gay life, The Sparsholt Affair becomes a meditation on human transience, even as it poignantly expresses the longing for permanence and continuity."--